2016
DOI: 10.5144/0256-4947.2016.269
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of a quality-of-life assessment instrument in children aged between 6 and 11 years

Abstract: BACKGROUNDThere is increasing recognition of the importance of obtaining children’s reports of their health, but significant challenges remain in accomplishing these goals in a systematic, community-based approach.OBJECTIVESThe aim of study was to evaluate the validity and reliability of the culturally adapted Turkish version of the “Child Health and Illness Profile – Child Edition (CHIP-CE) (6–11) for children 6 to 11 years of age.DESIGNCross-sectional analytical study conducted at Eskisehir Osmangazi Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Past studies have validatedthe reliability of FQoLSin measuring quality of family life [30–32] . The internal consistency (Cronbach's α) ranges from .88 to .94. supporting the authenticity of FQoLS, evidence showed that the validity and reliability proof also cut across cultures and countries [33] …”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…Past studies have validatedthe reliability of FQoLSin measuring quality of family life [30–32] . The internal consistency (Cronbach's α) ranges from .88 to .94. supporting the authenticity of FQoLS, evidence showed that the validity and reliability proof also cut across cultures and countries [33] …”
Section: Methodsmentioning
confidence: 74%
“…[30][31][32] The internal consistency (Cronbach's a) ranges from .88 to .94. supporting the authenticity of FQoLS, evidence showed that the validity and reliability proof also cut across cultures and countries. [33] 2.5. Participants and procedure…”
Section: Dependent Measurementioning
confidence: 99%
“…The internal consistency (Cronbach's α) ranges from 0.88 to 0.94. The validity and reliability of FQol have proved its universal acceptability in many countries including Albania, Bahasa Malaysia, Cantonese, Australia, Brazil, Canada, Israel, India, South Africa, and the United States (Demirsoy & Sayligil, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…After the completion of the Delphi method, refinement of the questions within each domain was undertaken using the available tools. It was decided to include the Child Health and Illness Profile -Child Edition, CHIP-CE (Version 1.0) tool in its entirety within the questionnaire as this tool included measures for both caregivers and children, has been translated into 38 languages and has undergone reliability and validity testing in various countries including USA, Turkey and multiple countries in Europe [17][18][19][20] and covered many of the domains and subtopics identified from the Delphi method. The CHIP-CE (Version 1.0) predominantly uses a recall period of 4 weeks, with five-point Likert scale responses (1 = never, 2 = almost never, 3 = sometimes, 4 = almost always, 5 = always, or 1 = no days, 2 = almost no days, 3 = some days, 4 = almost every day, 5 = every day).…”
Section: Questionnaire Developmentmentioning
confidence: 99%